ANALYSIS OF CONSUMER SATISFACTION LEVEL OF INDOMIE BRAND INSTANT NOODLE PRODUCTS IN EAST LOMBOK REGENCY - Nining Faperta; Rizal Ahmadi (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
The purpose of the study was to determine the level of community satisfaction with the attributes of the Indomie brand instant food products in East Lombok Regency and the attributes of the Indomie brand instant food which have consumer satisfaction and collective interests. Determination of the location of the study deliberately in East Lombok Regency. The research objective estimation method uses the Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and Conjoint analysis. The results of the analysis show that the attributes of the Indomie brand of instant food with a high level of consumer satisfaction include halal labels, taste, clarity of expiration, information on nutritional values, and ease of access (marketing). Overall, the instant food attributes of the Indomie brand provide consumer satisfaction with a value of 76.64% which is included in the satisfied criteria. While the conjoint method estimates the most important factor and has a high usability value, namely quality with a coefficient of importance value of 47% at the product packaging level, product texture, and product color, the price attribute has a value of 22.6% at the selling price level and the price is appropriate. quality, while the service quality attribute with a value of 11.5% at the level of customer service numbers